Software-defined network technology for learning in research and education groups - Silva, José (2021)
Software Defined Network (SDN) is an emerging and programmable network paradigm that changes the way networks are designed and managed by introducing an abstraction that decouples control from the data plane. This technology has generated great interest in both industry and academia. SDN aims to simplify network management while allowing students, teachers, and researchers to experiment with protocols on networks that are used on a daily basis. In addition, it has led to the emergence of new trends in educational systems, especially the university sector, in computer systems and network administration. Due to the little diffusion of the SDN and the high projection that this technology currently has, it is essential that the university educational entities are those that dabble in this issue. That is why this essay is a synthesis that addresses the importance of applying SDN for educational purposes and in the context of academic research groups.